A companion to heresy inquisitions - Prudlo, Donald (Brill's companions to the Christian tradition, 2019)
Inquisitions of heresy have long fascinated both specialists and non-specialists. 'A Companion to Heresy Inquisitions' presents a synthesis of the immense amount of scholarship generated about these institutions in recent years. The volume offers an overview of many of the most significant areas of heresy inquisitions, both medieval and early Modern. The essays in this collection are intended to introduce the reader to disagreements and advances in the field, as well as providing a navigational aid to the wide variety of recent discoveries and controversies in studies of heresy inquisitions